Crack growth behavior and thermal shock resistance of ceramic sandwich structures with an auxetic honeycomb core. (15th March 2021) - Hu, J.S.; Wang, B.L.
Abstract: This paper developed a thermal–mechanical analysis model to describe the thermal shock behavior of ceramic sandwich structures (CSSs) with an auxetic honeycomb core. The transient temperature distribution and the associated thermal stress field of CSSs subjected to a thermal shock were determined. The crack growth behavior was discussed based on the thermal stress intensity factor (TSIF), crack location, face-sheet thickness, and internal cell orientation of the honewycomb core in detail. The results revealed that the auxetic and non-auxetic honeycomb cores have the similar temperature distribution profile however the auxetic honeycomb core can substantially reduce the overall thermal stress level. Furthermore, by equating the maximum TSIF and equivalent fracture toughness, the critical temperature for which the honeycomb core can sustain without failure was obtained. The results showed that CSSs with auxetic honeycomb core possessed a higher thermal shock resistance than that of non-auxetic. This research work was the first attempt to identify the the thermal shock resistance of CSSs with an auxetic honeycomb core. The results would provide fresh insight into the design and selection of CSSs applied in an extreme temperature environments.